Correction: Sato-Akushichi et al. Choroidal Volume Evaluation after Photodynamic Therapy Using New Optical Coherence Tomography Imaging Algorithm. Pharmaceuticals 2021, 14, 1140 - Miki Sato-Akushichi; Shinji Ono; Gerd Klose; Youngseok Song (MDPI AG, 2022)
Error in Figure [...]